TGF-β/Smad Signaling Pathway in Tubulointerstitial Fibrosis - Yu, Xiao-Yong; Sun, Qian; Zhang, Ya-Mei; Zou, Liang; Zhao, Ying-Yong (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) was a major public health problem worldwide. Renal fibrosis, especially tubulointerstitial fibrosis, is final manifestation of CKD. Many studies have demonstrated that TGF-β/Smad signaling pathway plays a crucial role in renal fibrosis. Therefore, targeted inhibition of TGF-β/Smad signaling pathway can be used as a potential therapeutic measure for tubulointerstitial fibrosis. At present, a variety of targeting TGF-β1 and its receptors as well as its downstream Smad proteins and Smad-dependent long non-coding RNAs (lncRNAs) expression regulators have attracted increasing attention. Natural products used as potential therapeutic strategies for tubulointerstitial fibrosis have the characteristics of acting on multiple targets by multiple components and few side effects. With the continuous research and technique development, more and more mechanisms of action of natural products have been discovered, and there are many researches on the inhibition of tubulointerstitial fibrosis by natural products via TGF-β/Smad signaling pathway. This review focuses on the introduction of the role of TGF-β/Smad signaling pathway in tubulointerstitial fibrosis and potential therapeutic strategies of natural products targeting TGF-β/Smad signaling pathway against tubulointerstitial fibrosis. Additionally, many challenges and opportunities are presented for inhibiting renal fibrosis in the future.